PEMANFAATAN APLIKASI GEOGEBRA DALAM PEMBELAJARAN KALKULUS I PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA, UNIVERSITAS TIMOR - Justin Eduardo Simarmata; Debora Exaudi Sirait (Universitas Islam Sumatera Utara, 2020)
To find out the increase in the ability of mathematical understanding in learning calculus I semester II students of mathematics education study programs on the subject of functions and limits, we need a learning media in the form of Geogebra applications. Geogebra applications is one of the calculus I learning media that can be used to demonstrate or visualize mathematical concepts as well as a tool to construct concepts mathematically. The sample in this study was 54 seconds semester students of the mathematics education study program, Faculty of Education, University of Timor using purposive sampling techniques. The method used in this study is a pre-experimental method with one group pretest-posttest design. Analysis of the data in this study used the non-parametric Mann Whitney test. Based on the results of the N-gain score test, it shows that the average N-gain score is 58.4251 or 58.4%, which results are included in the quite effective category. Thus, the use of Geogebra applications in learning calculus I in the second-semester students of mathematics education study programs is quite effective in improving students' mathematical understanding of learning calculus I.